PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PROBLEM BASED LEARNING PADA MATERI BILANGAN DI KELAS VII SMP NEGERI 22 KOTA JAMBI - . relawati (Universitas Batanghari Jambi, 2017)
This research is based on the sample of the problem on the Student Worksheet (LKS) is still lack of structured steps of work, the exercise problem is not related to everyday life. This research is a development research. Products developed in the form of Student Worksheet (LKS) mathematics on the number material for SMP class VII with problem based learning model. The development model used is the ADDIE model consists of several stages: Analyze, Design, Development, Implementation, and Evaluation. Validation was done by 2 material experts, design experts and media experts. The Student Working Sheet (LKS) developed was tested in 3 stages, one to one learner with 3 subjects, small group trials (small Group try-out) with the subject of 6 students, field trials (field try-out) with the subject of 36 students. The results showed that the Student Worksheet (LKS) problem based on problem based learning based on the assessment: 1) material experts obtained The average total of 3.98 is included in the